TESTS FOR ASSESSING ACCURACY IN BASKETBALL - A SYSTEMATIC REVIEW - Srđan Prodanović; Goran Jelaska; Marta Tomljanović (The Sky, 2022)
Basketball is a sport where the success of sports performance is reflected in the possession of technical-tactical and motor skills. Basketball shooting, which is closely related to accuracy, was previously recognized as the most frequently used and most important technique in the game. When it comes to precision, in basketball we talk about situational precision, which is seen as an integral part of technique, and it is necessary to evaluate and develop it in this way. For this reason, precision screening is a very important parameter when developing a training program. The following index databases were used to collect adequate literature: GoogleScholar, PubMed, MEDLINE. During the search, the following keywords were used: basketball, accuracy, tests, baskteball, accuracy, testing, shooting tests. During the analysis and evaluation of the research, 16 researches were selected that corresponded to the topic and were included in the research. All 16 studies completely met the inclusion criteria. It can be concluded that the most frequently applied measuring instruments/tests in assessing the accuracy of basketball players are: shooting from the free throw line in 60 seconds, dynamic test of free throws in 60 seconds, jump shot tests in static and dynamic conditions, test of throwing from the free throw line, but also throwing from the left and right side of the free throw line, i.e. in the 2-point area, as well as the throw/jump shot test from the 3-point line.